2018
DOI: 10.1183/13993003.01616-2018
|View full text |Cite
|
Sign up to set email alerts
|

Escaping the Plato's cave of latent tuberculosis testing: a path for developers of predictive tests for risk of tuberculosis

Abstract: @ERSpublicationsThe End TB Strategy calls for renewed focus on latent TB, which requires development of more predictive tests. KIK et al. provide a framework for the clinical development of such tests, an ambition that calls for joint efforts by researchers and funders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…6 With IGRAs being poor predictors of development of active tuberculosis, 7 a test for incipient tuberculosis is on the most-wanted diagnostics list. 8,9 Assessment of the stage of infection could be achieved through testing responses to stage-specific antigens, such as latency antigens, resuscitation promoting factors, and replication associated antigens. 10 Other possible targets are cytokines other than interferon-, 11 specific T-cell populations, or host biomarkers, such as prognostic correlates of risk www.thelancet.com/infection Vol 19 February 2019 based on mRNA expression signatures, which are now being evaluated for prediction of active tuberculosis.…”
Section: New Developments On Interferon-γ Release Assays For Tubercul...mentioning
confidence: 99%
“…6 With IGRAs being poor predictors of development of active tuberculosis, 7 a test for incipient tuberculosis is on the most-wanted diagnostics list. 8,9 Assessment of the stage of infection could be achieved through testing responses to stage-specific antigens, such as latency antigens, resuscitation promoting factors, and replication associated antigens. 10 Other possible targets are cytokines other than interferon-, 11 specific T-cell populations, or host biomarkers, such as prognostic correlates of risk www.thelancet.com/infection Vol 19 February 2019 based on mRNA expression signatures, which are now being evaluated for prediction of active tuberculosis.…”
Section: New Developments On Interferon-γ Release Assays For Tubercul...mentioning
confidence: 99%
“…In 2016, the global prevalence of LTBI was updated to 23%, which corresponds to 1.7 billion people infected worldwide [ 6 ]. Studies have shown that <3% of these people will develop active TB over the course of their lifetime, the risk being 20–100 times higher among PLHIV [ 4 , 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%